The Influence of Price Perception and Product Quality Perception on Indomie Purchasing Decisions in Surabaya - Aksanul Fikri; Hery Pudjoprastyono (International Journal of Economics (IJEC), 2023)
This study aims to identify how the influence of price perceptions and product quality perceptions on purchasing decisions for Indomie in Surabaya . The population of this research is consumers of Indomie products. This research method is quantitative by taking a sample of 88 respondents and distributing questionnaires in the city of Surabaya with the Google Forms. The sample collection technique uses non-probability sampling with purposive sampling method. The sample consists of respondents who live in Surabaya, aged minimum 17 years and over, buyers and consumers who have consumed Indomie . The analysis technique used in this study uses Partial Least Square (PLS). Based on the results of data processing from this study, it can be concluded that the decision for Indomie in Surabaya is positively and significantly influenced by the price perceptions and product quality perceptions variables.